Her best-kept secret : why women drink-- and how they can regain control - Glaser, Gabrielle (Simon & Schuster, 2013)
Looks at the cultural factors contributing to a rise in alcoholism among today's women and compares today's practices to those of earlier generations while noting the current ineffectiveness of AA and other mainstream treatments.